Acute Toxicity Assay Based on Electrochemical Method for Detection of Antibiotic Residues in Water. Issue 2 (7th July 2022) - Dong, Jia; Chang, Xin; Li, Donghui; Liu, Chang
Abstract: In this work, the bacteria suspended in solution or immobilized in the biofilm were employed to study whether bacterial electrochemistry can reflect the impacts of the antibiotic residues in water on microorganisms. In the sensing system with immobilized bacteria, the tested antibiotics of 10∼40 mg/L showed an opportunity to inhibit respiration over a short time and the combined effect of these antibiotics exhibited a complex dose‐dependence. The resistance was induced for the immobilized bacteria in the repeated measurement over a long‐term period, which was fortunately solved by refreshing the biofilm via a nutrient supplementation. In the solution system, bacterial respirations were promoted by the tested antibiotics even at concentrations up to 160 mg/L, but β‐glucosidase activity was inhibited by only 0.05 mg/L antibiotic. Cu 2+ and Zn 2+ were further inducted in the suspended system, and the combination of metals and antibiotics showed an obvious antagonistic effect. Real water detection indicated that the bacterial electrochemical method was expected to warn the water qualities with a sudden change by an appropriate testing condition. Abstract :